2001
DOI: 10.1177/03635465010290010701
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Patellofemoral Osteoarthritis and Associated Findings 7 Years after Anterior Cruciate Ligament Reconstruction with a Bone-Patellar Tendon-Bone Autograft

Abstract: To evaluate the development of postoperative patellofemoral osteoarthritis, we performed a retrospective clinical and radiographic study of 100 patients who had undergone anterior cruciate ligament reconstruction with a bone-patellar tendon-bone autograft an average of 7 years before the follow-up. Radiographic evaluation showed no patellofemoral osteoarthritis in 53 patients (group I), mild osteoarthritis in 34 patients (group II), moderate osteoarthritis in 12 patients, and severe osteoarthritis in 1 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
79
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 25 publications
(31 reference statements)
9
79
3
2
Order By: Relevance
“…More specifically, PF arthritis presents constantly with AKP, and other authors have documented that patients with established PF arthritis that required surgical treatment had a history of significantly higher AKP than controls (22 % vs 6 %, p<0.001) [48]. The risk of long-term arthritis after ACL reconstruction has been questioned in the literature, and the possibility of PF arthritis following ACL reconstruction has been recently re-emphasized [49][50][51]. Järvelä et al documented mild to severe PF osteoarthritis in 88.6 % of their patients seven years after ACL reconstruction [49] and also correlated the increased incidence of AKP in this group but, unfortunately, without evaluating for the presence of trochlear dysplasia in these patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, PF arthritis presents constantly with AKP, and other authors have documented that patients with established PF arthritis that required surgical treatment had a history of significantly higher AKP than controls (22 % vs 6 %, p<0.001) [48]. The risk of long-term arthritis after ACL reconstruction has been questioned in the literature, and the possibility of PF arthritis following ACL reconstruction has been recently re-emphasized [49][50][51]. Järvelä et al documented mild to severe PF osteoarthritis in 88.6 % of their patients seven years after ACL reconstruction [49] and also correlated the increased incidence of AKP in this group but, unfortunately, without evaluating for the presence of trochlear dysplasia in these patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of long-term arthritis after ACL reconstruction has been questioned in the literature, and the possibility of PF arthritis following ACL reconstruction has been recently re-emphasized [49][50][51]. Järvelä et al documented mild to severe PF osteoarthritis in 88.6 % of their patients seven years after ACL reconstruction [49] and also correlated the increased incidence of AKP in this group but, unfortunately, without evaluating for the presence of trochlear dysplasia in these patients [6]. Oiestad et al documented 26 % of established PF arthritis 12 years after ACL reconstruction, again without checking for the pre-operative presence of similar radiological findings such as trochlear dysplasia [51].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several authors have shown increasing functional instability and degenerative radiographic changes after single-bundle ACL reconstruction. 20,30,35 The current trend in ACL reconstruction techniques is to more closely restore the anatomical footprint and kinematics of the ACL through a more laterally positioned femoral tunnel, which replaces portions of both the PL and AM bundles. 10,25 Clinical outcome studies in patients using lateralized single-bundle femoral tunnel ACL reconstruction techniques have yielded good results.…”
Section: Discussionmentioning
confidence: 99%
“…The use of autografts does have its drawbacks due to harvesting and donor site morbidity. Furthermore, autograft harvesting increases operating time, and gives rise to the risk of patella fracture, patella tendonitis and residual tender scars [12]. On the other hand, advantages such as the unlimited supply of grafts, diminished surgical time and the absence of donor site morbidity [23] make allografts a very interesting option.…”
Section: Discussionmentioning
confidence: 99%